Implementasi Methontologi Untuk Pembangunan Model Ontologi Pada Sistem Informasi Produk Bodycare - Ida Ayu Taria Putri Mahadewi; Ida Bagus Gede Dwidasmara (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
There are many different body care products on the market. This certainly causes many considerations to choose the right body care products and according to the needs or skin problems of each individual. The solution that can be done to this problem is to use a semantic ontology model with the Methontology method. This bodycare product ontology development model produces 10 classes, 5 Object Properties, 5 Data Properties, and 45 individuals. The ontology evaluation process by performing SPARQL query which is used to get the appropriate results. Keywords: Bodycare, Ontology, Methontology, SPARQL, Protégé.